SENSORY ANALYSIS OF STARCH GARUT UTILIZATION (MARANTHA ARUNDINACEA L.) AS SUBSTITUTION MATERIAL FOR WHEAT FLOUR IN MAKING PASTA - Enceng Sobari (Agroindustrial Technology Journal, 2023)
The purpose of this study was to determine the effect of arrowroot starch substitution on pasta making. The benefit of this research is that it can determine the effect of arrowroot starch substitution in the panelist preference level in starch content. The formulations used are arrowroot starch P1 50% and flour 50%, P2 arrowroot starch 70% and wheat flour 30%, P3 arrowroot starch 100 and wheat flour 0%. The parameters observed were sensory test of color, aroma, taste, texture and starch content. Data processing of hedonic test uses kruskawalis test analysis and duncan follow-up test. Starch content test data were analyzed using Analysis of Variance (ANOVA) the use of arrowroot starch as a substitution material affected the aroma and texture. Starch levels have decreased due to processing. The best treatment in the hedonic test process of arrowroot paste processing was obtained by adding 50% starch formulation and 50% flour while in starch carbohydrate test was obtained by adding 100% starch and 0% flour.